Pelatihan Penilaian Aset Bagi Perangkat Desa Pandesari - Lustina Fajar Prastiwi,; Nasikh,; Sugeng Hadi Utomo,; Emma Yunika Puspasari, (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this community service activity is to provide socialization and training to strengthen understanding in calculating and knowing the value of village assets and their calculation techniques. This activity takes place in 3 stages, namely socialization, training and implementation. The socialization activity aims to introduce asset and property valuation theory. Followed by training activities that aim to provide further introduction to the techniques and applications for valuing village assets and property, as well as their implementation in calculating village assets. The result is that the training and implementation of asset appraisal carried out by the service team can increase understanding of the theory of asset and property valuation.